PolDrugs 2025: results of the third edition of the nationwide study on psychoactive substance use in the context of psychiatry and harm reduction - Marek, Julia; Domek-Gumprecht, Magdalena; Macionga, Agata; Szafoni, Sandra; Więckiewicz, Gniewko (Frontiers in Psychiatry, 2025)
IntroductionPolDrugs is a biennial epidemiological study aimed at analyzing patterns of mostly illicit psychoactive substance use in Poland in the context of psychiatry and harm reduction. This survey was held for the third time, and its results were compared to the last two editions.Materials and methodsThe survey was conducted as an online survey with 37 closed-ended single-choice questions and 3 multiple-choice questions. Respondents were recruited through outreach on social media platforms, primarily Facebook and Instagram, in drug-related groups. Recruitment efforts were supported by activists and advocacy groups who promoted the questionnaire through their own social media networks. The sample consisted of 2,447 people between the ages of 13 and 63 years. Statistical analysis included descriptive statistics only.ResultsThe study population (mean age 27 years) was predominantly male and urban. Marijuana was the most common substance used after alcohol, caffeine, and nicotine, though overall consumption was infrequent (35.6% reporting use once every few months or less) and mainly occurred in social settings (50.2%) or at home (52.3%). Notably, 83.6% never tested substance composition, and 51.4% relied on visual estimation for dosing. Sixty percent had neglected daily responsibilities, while 16.8% faced legal issues. Although 70.7% had not sought medical help, nearly half had seen a psychiatrist (primarily for depression), with 41.1% of these having attempted suicide and 70.5% using illicit substances before their initial consultation. Only 40% consistently disclosed their substance use to a physician.ConclusionsStimulant use and subsequent medical consultations—particularly for mephedrone derivatives—are rising warranting further investigation. The proportion of respondents who use psychoactive substances alone is increasing, now exceeding 25%. Psychedelic use is declining possibly due to reduced mainstream media attention. The observation also shows a growing acceptance of psychiatric care in Polish society.